A repeatedly evolved mutation in Cryptochrome-1 of subterranean animals alters behavioral and molecular circadian rhythms - Amruta Swaminathan; Alexander Kenzior; Andrew Price; Hua Li; Colin McCoin; Aurélie Hintermann; Kyle Weaver; NatiCia Morris; Alex C. Keene; Nicolas Rohner (iScience)
Summary: Independent lineages showing similar phenotypic traits can use different genetic paths to achieve the same phenotypic outcome. Instances of such convergence at the genotypic level, however, remain underexplored. In this study, we generated and used a homozygous knock-in mouse model to characterize a previously identified mutation, CRY1 R263Q, that has repeatedly evolved in a highly conserved protein domain across lineages adapted to caves and subterranean environments. Indirect calorimetry experiments revealed that the mutation alters circadian patterns of energy expenditure, locomotor activity, and feeding behaviors in the dark phase, but no further metabolic phenotypes. We also found that the mutation causes the aberrant expression of canonical circadian and metabolic genes in the liver, consistent with circadian clock and metabolic dysregulation reported in subterranean dwellers, which may be adaptive in such environments. Our work highlights the capacity for selection to drive repeated phenotypic evolution through repetitions of the same underlying genetic change.